Effects of 2-ketoisocaproate on insulin release and single potassium channel activity in dispersed rat pancreatic beta-cells. - Ashcroft, F; Ashcroft, S; Harrison, D (1987)
1. The effects of the insulin secretagogue 2-ketoisocaproate, and of arginine, on insulin release, intracellular adenosine triphosphate (ATP) concentration and the activity of single K channels in cell-attached membrane patches have been studied in primary cultures of beta-cells from adult rat islets of Langerhans. 2. Insulin secretion was significantly increased by 2-ketoisocaproate (20 mM). The time course of this release was biphasic. Arginine (20 mM) did not stimulate insulin secretion. 3. In the absence of 2-ketoisocaproate (or arginine), two kinds of K channel were regularly observed in cell-attached membrane patches held at the cell resting potential: a channel of approximately 20 pS conductance and a channel of 50 pS conductance ([K]o = 140 mM, room temperature). 4. Addition of 2-ketoisocaproate (20 mM) to the bath suppressed the activity of the 50 pS channel and initiated action potentials. Arginine (20 mM) was without effect. 5. The intracellular concentration of ATP was increased significantly by 2-ketoisocaproate (20 mM) but not by arginine (20 mM). 6. It is suggested that, like glucose, 2-ketoisocaproate depolarizes the beta-cell and mediates insulin secretion by reducing the open probability of the 50 pS K channel. The results are also consistent with the idea that both secretagogues inhibit this channel by increasing the cytoplasmic concentration of ATP.